Objects, Things and Clues in Early Twentieth-Century Fiction. Issue 2 (May 2019) - Stewart, Victoria
Abstract : Despite their different aesthetics both modernism and detective fiction engage with, refashion and, at times, critique realism, and the description of objects is central to this. Tracing how certain types of object and relationships with objects feature in works by Virginia Woolf and Agatha Christie in the 1920s reveals that for each author, descriptions of interiors, and particularly the stuff that individuals accumulate in their homes, is central, and the presence of belongings vies with the absence of their owners. Considering the valences of furniture, scrap paper and curios shows how possessions continue to speak of the real even in writing that challenges realist modes of representation.